Implementasi Manajemen Asset Pada Tiang Distribusi Listrik Jaringan Tegangan Rendah Dan Jaringan Tegangan Menengah Dengan Memanfaatkan Aplikasi Qgis (Quantum Geographic Information System) - Rahma Farah Ningrum (Sekolah Tinggi Teknik - PLN, 2015)
Power distribution network continues to grow all the time without stopping. Indonesia along with population growth, this growth requires additional asset JTR pole (Low Voltage Network) and JTM (Medium Voltage Network) is adequate. So that all citizens can enjoy it. Location spread tiangpun increasingly widespread. The consequence is that asset management pillar good network and can simplify asset tracking. Implementation of asset management application using QGIS (Quantum Geographic Information System) is required to trace the whereabouts of all assets existing poles in the region.